The organising vision for telehealth and telecare: discourse analysis. Issue 4 (19th July 2012) - Greenhalgh, Trisha; Procter, Rob; Wherton, Joe; Sugarhood, Paul; Shaw, Sara
Abstract : Objective: To (1) map how different stakeholders understand telehealth and telecare technologies and (2) explore the implications for development and implementation of telehealth and telecare services. Design: Discourse analysis. Sample: 68 publications representing diverse perspectives (academic, policy, service, commercial and lay) on telehealth and telecare plus field notes from 10 knowledge-sharing events. Method: Following a familiarisation phase (browsing and informal interviews), we studied a systematic sample of texts in detail. Through repeated close reading, we identified assumptions, metaphors, storylines, scenarios, practices and rhetorical positions. We added successive findings to an emerging picture of the whole. Main findings: Telehealth and telecare technologies featured prominently in texts on chronic illness and ageing. There was no coherent organising vision. Rather, four conflicting discourses were evident and engaged only minimally with one another's arguments. Modernist discourse presented a futuristic utopian vision in which assistive technologies, implemented at scale, would enable society to meet its moral obligations to older people by creating a safe 'smart' home environment where help was always at hand, while generating efficiency savings. Humanist discourse emphasised the uniqueness and moral worth of the individual and tailoring to personal and family context; it considered that technologies were only sometimes fit for purpose and could create as well as solve problems. Political economy discourse envisaged a techno-economic complex of powerful vested interests driving commodification of healthcare and diversion of public funds into private business. Change management discourse recognised the complicatedness of large-scale technology programmes and emphasised good project management and organisational processes. Conclusion: Introduction of telehealth and telecare is hampered because different stakeholders hold different assumptions, values and world views, 'talk past' each other and compete for recognition and resources. If investments in these technologies are to bear fruit, more effective inter-stakeholder dialogue must occur to establish an organising vision that better accommodates competing discourses.